2015
DOI: 10.1155/2015/815648
|View full text |Cite
|
Sign up to set email alerts
|

The Content of the 14 Metals in Cancellous and Cortical Bone of the Hip Joint Affected by Osteoarthritis

Abstract: The aim of the study was to determine the content of particular elements Ca, Mg, P, Na, K, Zn, Cu, Fe, Mo, Cr, Ni, Ba, Sr, and Pb in the proximal femur bone tissue (cancellous and cortical bone) of 96 patients undergoing total hip replacement for osteoarthritis using ICP-AES and FAAS analytical techniques. The interdependencies among these elements and their correlations depended on factors including age, gender, place of residence, tobacco consumption, alcohol consumption, exposure to environmental pollution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
30
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
9
30
2
Order By: Relevance
“…In our study, we observed statistically lower Fe concentration in the spongy bone of patients who consumed alcohol compared to patients who did not at 28.224 and 61.293 mg/kg dw, respectively. Zioła-Frankowska et al [53] also found lower Fe level in the cancellous bone of patients consuming alcohol; however the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In our study, we observed statistically lower Fe concentration in the spongy bone of patients who consumed alcohol compared to patients who did not at 28.224 and 61.293 mg/kg dw, respectively. Zioła-Frankowska et al [53] also found lower Fe level in the cancellous bone of patients consuming alcohol; however the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 90%
“…Knowledge of these relationships is important for the understanding of kinetic interactions of elements in the body [66]. Zioła-Frankowska et al [53] did not observed a correlation between Ni-Mo, Ni-Fe, and Fe-Mo in the femoral neck and head, whereas Dąbrowski et al [45] noted significantly positive Fe/Ni interaction in the bone. This research is the first to find a correlation among elements in the structures of the knee joint: Fe SB -Fe ACL , Fe SB -Ni SB…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations